Arabic and it's teaching to non-native speakers - Bahjat, Munjid Mustafa (s.n, 2012)
This research explores different studies in teaching Arabic to non-native speakers. It also comprises of numerous trends in learning, contains various learning skills, discusses method of training in teaching Arabic, investigates the features of perfection in developing Arabic learning programs, and examines the role of teaching in teaching Arabic literary texts for non-native speakers and finally reviews available literature on teaching Arabic